A case of chronic expanding hematoma in the oral floor. Issue 1 (January 2015) - Nagata, Masahide; Isomura, Emiko Tanaka; Sawai, Natsuko Yoshimura; Higuchi, Masataka; Ohtani, Satoko Matsuda; Aikawa, Tomonao; Okura, Masaya
Abstract A chronic expanding hematoma (CEH), a type of lesion that gradually develops after trauma or surgery, can appear in many locations, though occurrence in the head and neck region is uncommon. Here, we report the first known case of a CEH arising in the oral floor, which developed in a 16-year-old woman who exhibited a slowly expanding mass over a period of 2 months after dental treatment.